Comparison of Two Conventional Methods for Identification of Dermatophyte Fungi - Salim Naseif Alzubaidy, Tiba; Jasim Mohammed, Abdulameer; Abbas Hasan Al-Gburi, Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The current study is the identification and isolation dermatophyte species in clinical isolates by both Sabouraudâ€™s Dextrose Agar (SDA) and on Dermatophyte Test Medium (DTM). Clinical specimens of hair, nails and skin scales were collected from patients with dermatophytosis and submitted to direct microscopic examination after immersion in 20% of potassium hydroxide solution. The clinical specimens were cultured on SDA containing chloramphenicol and cycloheximide, and on DTM. Tinea corporis showed the highest prevalent dermatophyte infection among patients (26.7%), followed by Tinea pedis (23.3%), whereas Tinea manuum exhibited the lowest fungal infection (6.7 %). Rural areas revealed the highest prevalence of dermatophyte infection (70.0 %) in comparison to 30.0% in urban areas. Based on the conventional laboratory methods, 30 clinical isolates of dermatophytes showed positive cultures which belong to three genera (Trichophyton, Microsporum and Epidermophyton). Trichophyton mentagrophytes was the most common species (21.7%) isolated among 30 positive dermatophytes, followed by Epidermophyton flocosum (17.4%), then Trichophyton bullosum and Trichophyton tonsurans (13.0%).